Prompting Legislative Agreement and Loyalty: What Role for Intra-Party Democracy?. Issue 2 (22nd February 2018) - Close, Caroline; Gherghina, Sergiu; Sierens, Vivien
Abstract: Existing research often suggests that a greater degree of internal democracy within parties could weaken party unity. This article tests this assumption and analyses the relationship between degrees of intra-party democracy (IPD) and legislators' attitudes towards party unity. The article uses data collected in the framework of the PartiRep Comparative MP Survey; and of the Political Party Database (PPDB). The study includes 796 parliamentarians in 45 parties, elected in 14 European national assemblies. The findings indicate that the legislators from more democratic party organizations tend to report more frequent disagreement and to assert their own opinions against the one of their parties.